1999
DOI: 10.1002/(sici)1096-9918(199902)27:2<98::aid-sia476>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Study on interfacial reaction of Ti/AlN by SIMS, RBS and XRD

Abstract: A 200 nm Ti film was deposited on a polished AlN ceramic substrate at 200 °C by electron beam evaporation and then annealed under high vacuum conditions. The MCs+‐SIMS technique (detecting MCs+ secondary ions under Cs+ primary ion bombardment, where M is the element to be analysed), RBS and x‐ray diffraction (XRD) measurements were employed to probe the solid interfacial reaction between Ti and AlN from 200 °C to 850 °C, and the variation of interfacial composition distribution with annealing temperature and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…displayed the interfacial reaction zone of AlN/Ti after annealing at 1000°C/0.5 h, indicating the presence of δ‐TiN and α 2 ‐Ti 3 Al at the AlN/Ti interface. Some investigations 7,8,19 have reported that δ‐TiN and TiAl 3 are initially formed at the AlN/Ti interface after annealing between 600° and 800°C. Pinkas et al 8 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…displayed the interfacial reaction zone of AlN/Ti after annealing at 1000°C/0.5 h, indicating the presence of δ‐TiN and α 2 ‐Ti 3 Al at the AlN/Ti interface. Some investigations 7,8,19 have reported that δ‐TiN and TiAl 3 are initially formed at the AlN/Ti interface after annealing between 600° and 800°C. Pinkas et al 8 .…”
Section: Resultsmentioning
confidence: 99%
“…6(b). Excess Al atoms may proceed further beyond the α 2 ‐ Ti 3 Al layer into Ti, forming an α‐Ti(Al) solid solution and probably a two‐phase region (α‐Ti+β‐Ti), according to the Ti–Al–N ternary phase diagram 19 . While Al or N atoms diffuse into β‐Ti (A2, bcc) during annealing at 1000°C, the dissolution of up to 5 at.% Al and/or N atoms makes α‐Ti (A3, hcp) relatively stable with respect to β‐Ti.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the Ti-rich nitride would be formed. The radii of N, Ti and Al atoms are 0.07 nm, 0.1448 nm and 0.1431 nm [50], respectively, so nitrogen atoms diffuse mainly interstitially in the Ti lattice and should have a higher diffusion velocity than that of Al atoms which diffuse mainly by substitution. Because differences in diffusion velocities between Al and N atoms will result in a different gradient distribution in the diffusion direction, it can be assumed that titanium nitride was first formed in the nitrogen concentrated regions such as grain boundaries and then in the whole powder matrices.…”
Section: X-ray Diffraction Analysis and Reaction Mechanismmentioning
confidence: 99%